The effect of hydrogen peroxide (H2O2) on photosynthesis of Ficus deltoidea Jack var. trengganuensis Corner - Nashriyah, Mat; Abd Jamil, Zakaria; Mohammad Moneruzzaman, Khandaker; Norsyamila, Othman (2015)
A field experiment was conducted to evaluate the effect of hydrogen peroxide (H2O2 ) concentration on photosynthetic activity of Ficus deltoidea Jack var. trengganuensis Corner at FBIM farm, Terengganu. The plant was collected from Jambu Bongkok, Marang and propagated under sunlight-proof shade house. After 3 months, a total of 35 plants were selected and applied with 0 mM (as control), 5 mM, 10 mM, 15 mM and 20 mM H2O2 . The physiological activity was monitored monthly and measured during 10 am to 12 pm by using Handheld Photosynthesis System (CI-340, CID Inc., USA). Results showed that chlorophyll content, photosynthesis rate and carbon dioxide (CO2 ) accumulation of Ficus deltoidea var. trengganuensis were significantly increased after treated with 5 mM H2O2 . Besides that, other H2O2 treatments (10 mM, 15 mM and 20 mM) resulted in negative outcomes which is lower in photosynthetic activity as compared with control (0 mM H2O2 ). Thus, this study showed that application of definite concentration of H2O2 can increase the photosynthetic activity of Ficus deltoidea var. trengganuensis